1999
DOI: 10.1063/1.123048
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetics and magnetoresistance of a Permalloy point contact

Abstract: Room temperature magnetoresistance switching of Permalloy thin films induced by iron nanoparticles Appl. Phys. Lett. 92, 093121 (2008); Negative resistance contribution of a domain-wall structure in a constricted geometry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…5 for a NiFe layer of 30 nm in thickness for 0 M ef f = 1.064 T and A = 1.3ϫ 10 −11 J/m. 20 Therefore, in our finite-band PIMM and VNA-FMR setups, we cannot observe PSSW modes ͑P ജ 1͒. The FMR measurements at 22 and 35 GHz show that as the AF coupling strength decreases, the resonance field of the PSSW moves to lower values in the same manner as the optic mode and in good agreement with the theoretical models.…”
Section: Dynamic Measurements By Conventional Ferromagnetic Resonancesupporting
confidence: 71%
“…5 for a NiFe layer of 30 nm in thickness for 0 M ef f = 1.064 T and A = 1.3ϫ 10 −11 J/m. 20 Therefore, in our finite-band PIMM and VNA-FMR setups, we cannot observe PSSW modes ͑P ജ 1͒. The FMR measurements at 22 and 35 GHz show that as the AF coupling strength decreases, the resonance field of the PSSW moves to lower values in the same manner as the optic mode and in good agreement with the theoretical models.…”
Section: Dynamic Measurements By Conventional Ferromagnetic Resonancesupporting
confidence: 71%
“…Very carefully fabricated contacts, made by much the same method as in Ref. 327, using a nanohole in a membrane, were fabricated by Ozatay et al [385], who formed Ni-Ni contacts with one side exchange biased using FeMn. No effect larger than a fraction of a per cent was found (Fig.…”
Section: Experimental Explorationmentioning
confidence: 99%
“…They made calculations for Co [326] and Permalloy [327] and used these to estimate AMR and domain wall MR, using the Levy-Zhang model [183] for the latter term. In the case of NiFe they compared these to experimental data, and found marked discrepancies, failing even to reproduce the sign of the MR in one of the geometries they consider.…”
Section: Theoretical Interpretationmentioning
confidence: 99%
“…The boundary between the domains, the domain walls ͑DW's͒, are a source of magnetoresistance that recently has attracted experimental [1][2][3][4][5] and theoretical interest. [6][7][8] For ballistic systems, where the electron mean free path is longer than the system size, first-principles band-structure calculations have shown that the DW resistance is enhanced due to the nearly degenerate bands at the Fermi energy.…”
Section: Introductionmentioning
confidence: 99%